A Patient with Corneal Epithelial Disorder That Developed after Administration of a Latanoprost Generic, but Not a Brand-Name Drug, Eye Drop - Yukihisa Takada; Yuka Okada; Norihito Fujita; Shizuya Saika (Case Reports in Ophthalmological Medicine)
Background. We report a patient who developed corneal epithelial disorder repeatedly after changing the prescription from Xalatan eye drops (Pfizer Inc.) to Latanoprost eye drops (Kaken Pharmaceutical Co., Ltd.), both containing 0.005% latanoprost. Case Report. An 88-year-old male with glaucoma had been treated with Timoptol eye drops and Xalatan eye drops for a few years. While he stayed in a health care facility for the elderly, Xalatan eye drops was changed to Latanoprost eye drops usage, and eye pain developed on the day of this change. On the next day, he visited our department, and corneal epithelial disorder was observed. The drops were discontinued, and the corneal epithelial disorder healed after 2 days. Twenty days after the first consultation, Xalatan eye drops and Latanoprost eye drops were resumed by a physician of internal medicine in the health care facility, but eye pain developed again. After discontinuation of the two drugs, Xalatan eye drops usage was resumed the next day, but no corneal epithelial disorder was observed thereafter. Conclusions. This clinical history strongly suggested the association between a generic drug, Latanoprost eye drops, and the development of corneal epithelial disorder.